(3GdEeJGY HCMcGe GdSeGYs - (3LYaQ Hf KYdH (B( (3JZdH(B) (3Hf LYaQ GdCOahj, CHh GdaVd, ceGd GdOjf,J (B748 (3g` s
(3ChdgG (B:s
(3hHYO aEf CMcGe GdSeGY bO hbY GdfRGY ajgG ai SGda GdCYUGQ hJHGjfJ ajgG CbhGd YdeGA GdCeUGQ s
(3BNQgG (B:s
(3aEfi de CVY gPg GdQSGdI dg hdG dCeKGdg hGddg GdgGOi Edi ShGA GdSHjd hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLejYf s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B136s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B167s
Keywords: (3GdJUha hGdBOGH GdTQYjIs